Digital Technology in Physics Learning in the 21st Century: Study Literature Review - Irnin Agustina Dwi Astuti; Drajat Agung Nugroho; Mazda Rezki; Rahmi Novia Putri (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2024)
Digital technology has great potential to improve the quality of physics learning, especially in the 21st century. The implementation of digital technology aligns with the demands of 21st-century learning, which emphasizes the importance of technological literacy and adaptability to change. This research employs a literature review method, analyzing 200 research articles from the Google Scholar database spanning 2019-2024. The findings indicate that the most commonly used digital technologies in physics learning include Augmented reality (AR), digital comics, Virtual Laboratory, Virtual Reality (VR), Android, Google Sites, and Articulate Storyline. Digital technology allows easy and fast access to convey information and/or learning materials, and can improve students' digital literacy skills.